Preoperative platelet-albumin–bilirubin grades predict the prognosis of patients with hepatitis B virus-related hepatocellular carcinoma after liver resection: A retrospective study. Issue 12 (March 2018) - Luo, Hong-mei; Zhao, Shu-zhen; Li, Chuan; Chen, Li-Ping
Abstract : Abstract: Minimal information is available concerning platelet-albumin–bilirubin (PALBI) grades in patients with hepatocellular carcinoma (HCC) following liver resection. This study aimed to investigate the predictive ability of PALBI grades in patients with a Child–Pugh class A score and hepatitis B virus-related (HBV-related) HCC after liver resection. The data of patients with HBV-related HCC who underwent liver resection from 2010 to 2017 at our center were reviewed (n = 785). Cox regression was used to determine factors independently associated with postoperative recurrence and mortality. The area under the receiver operating characteristic curve (AUC) was used to estimate the predictive accuracy of different tools. During the follow-up period, 505 (64.3%) patients experienced recurrence, and 374 (47.6%) patients died. Multivariate analysis revealed that the tumor-node-metastasis (TNM) stage (HR = 1.591, 95%CI = 1.414–1.789, P <  .001), PALBI grade (HR = 1.326, 95%CI = 1.139–1.544, P <  .001), a high AFP level (HR = 1.382, 95%CI = 1.158–1.649, P <  .001) and transfusion (HR = 1.364, 95%CI = 1.087–1.712, P  = 0.007) were independently associated with recurrence. Additionally, microvascular invasion (HR = 1.674, 95%CI = 1.292–2.169, P <  .001), beyond the Milan criteria (HR = 0.477, 95%CI = 0.346–0.657, P <  .001), PALBI grade (HR = 1.356, 95%CI = 1.151–1.598, P <  .001), a high AFP level (HR = 1.542, 95%CI = 1.252–1.900, P <  .001), and transfusion (HR = 1.548, 95%CI = 1.199–1.999, P  = 0.001) adversely impacted the overall survival. The AUCs of the PALBI grades for postoperative recurrence and mortality were significantly higher than the albumin–bilirubin grade and Child–Pugh score. The prognostic significance of the PALBI grade for postoperative recurrence and mortality was maintained when stratified by the TNM stage. The preoperative PALBI grade is a surrogate marker for the postoperative prognosis in patients with HBV-related HCC after liver resection.